Characteristics Analysis of Reactive Power for Metro Power Supply System and Its Compensation Design - 周方圆; 黄燕艳; 龙礼兰; 周靖; 邱文俊 (Kongzhi Yu Xinxi Jishu)
It introduces the main structure of metro power supply system and builds up its equivalent loads model. With the typical analysis of reactive power compensation characteristics of the loads for metro power supply system and its main effects to the grid, a compensation strategy of reactive power is proposed accordingly. The strategy is verified by taking the reactive power compensation of an urban metro project as an example and the result is well.